2021
DOI: 10.1108/jidob-09-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and institutional risk in a secure developmental disorder service: does the SAVRY inflate risk in adolescents exposed to ACEs?

Abstract: Purpose Adverse childhood experiences (ACEs) are highly prevalent in people with developmental disorders who engage in offending behaviour. Many violence-based risk assessment tools include items pertaining to ACEs, and may inflate risk scores in trauma-exposed groups. This paper aims to explore the relationships between ACEs, risk assessment scores, incidents of risk and restrictive practices, in adolescents with developmental disorders in a forensic inpatient setting. Design/methodology/approach Secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Theme 6: Constraints of a secure environment and lack of control (11 articles, 19%) There were various factors deemed important in the secure environment that increased the risk of self-harm. For example, waiting for things (Selenius and Strand, 2017), use of restraints and penal measures (S ˇendula-Jengi c et al, 2004;Webb et al, 2022) and not having access to preferred items or substances, such as nicotine (Zhong et al, 2019). Further factors included being locked in (Liebling et al, 1997) and isolation (Challinor et al, 2021).…”
Section: Analysis Of Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…Theme 6: Constraints of a secure environment and lack of control (11 articles, 19%) There were various factors deemed important in the secure environment that increased the risk of self-harm. For example, waiting for things (Selenius and Strand, 2017), use of restraints and penal measures (S ˇendula-Jengi c et al, 2004;Webb et al, 2022) and not having access to preferred items or substances, such as nicotine (Zhong et al, 2019). Further factors included being locked in (Liebling et al, 1997) and isolation (Challinor et al, 2021).…”
Section: Analysis Of Themesmentioning
confidence: 99%
“…Approximately a fifth of articles identified that those who engaged in self-harm also engaged in aggression directed at others and objects, termed dual harm (Hillbrand et al , 1994; Nijman and à Campo, 2005; Selenius and Strand, 2017; Šendula-Jengić et al , 2004; Verstegen et al , 2020; Webb et al , 2022). It was noted that this was especially the case for those who repeatedly engaged in self-harm, with the aggression they displayed more severe than for those who did not self-harm (Hillbrand et al , 1996; O’Shea et al , 2014) Long et al (2012) noted that those who were transferred from prison to a secure hospital also displayed elevated levels of aggression to others, during the first six months following transfer.…”
Section: Analysis Of Themesmentioning
confidence: 99%
“…Similarly, some have argued that those risk factors involving adverse childhood events (Webb 2022) (e.g. early caregiver disruption) erroneously cause higher risk ratings in those with developmental disorders, as these populations are known to experience higher rates of traumatic events.…”
Section: Risk Assessment In Mental Healthcarementioning
confidence: 99%